Strategi Membangun Karakter Anak Usia Sekolah Dasar (Telaah Kritis Buku “Alhamdulillah Anakku Nakal” Karya Miftahul Jinan dan Choirus Syafruddin) - Huzuwah, Huzuwah; Ichsan, Ahmad Shofiyuddin; Yunianta, Rohmat Dwi (Al-Fikru: Jurnal Ilmiah, 2021)
A naughty child is a test from God who has to be lived with the right solution. So, parents should be grateful if they haave a naughty child. This research aims to determine the strategy to build the child character of elementary school in the book "Alhamdulillah Anakku Nakal" by Miftahul Jinan and Choirus Syafruddin. This research type is library research and the method used in data collection is the documentation. The results of this research explained that to create a good success in character education of children in a family, in addition to how to educate or proper parenting, as parents need a strategy in building the child character of elementary school. The strategies used include: (1) creating an atmosphere filled with comfort and affection, (2) inviting children to feel what others feel, (3) reminding the importance of affection between family members, (4) using habituation methods, and (5) making them accustomed to good behavior. The contributions of contemporary education in this book include: (1) building a mindset whose paradigm is about bad attitudes from children to be good, 2) parents become more relaxed, wise, and calmer seeing children’s behavior that is not in accordance with their wishes, and (3) parental remorse due to wrong actions.